2010
DOI: 10.1001/archneurol.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Population-Based Study of Psychosis in Parkinson Disease

Abstract: To investigate the prevalence, incidence, risk factors, and concomitants of Parkinson disease (PD)associated psychosis (PDP) in a population-based prevalent cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
211
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(228 citation statements)
references
References 40 publications
6
211
2
9
Order By: Relevance
“…Although hallucinations did not occur in the placebo group, they commonly occur in PD, and additional factors such as age, cognitive impairment, other co‐morbidities, or concomitant medications also may influence the risk of this event in this population 13, 14…”
Section: Discussionmentioning
confidence: 83%
“…Although hallucinations did not occur in the placebo group, they commonly occur in PD, and additional factors such as age, cognitive impairment, other co‐morbidities, or concomitant medications also may influence the risk of this event in this population 13, 14…”
Section: Discussionmentioning
confidence: 83%
“…Hallucinations are the most common manifestation, and they affect up to 40 percent of patients, particularly those with dementia (29,30). As we saw, the prevalence and severity of hallucinations in PD is higher in elderly patients, progressing over time.…”
Section: Discussionmentioning
confidence: 58%
“…Contrary to these studies, a 12-year study found that higher LED was associated with increased future risk of psychosis. 13 The overall evidence coupled with clinical experience has led dopaminergic therapies to be considered modifiers of psychosis in PD.…”
Section: Medicationsmentioning
confidence: 99%
“…A number of studies found an association between visual hallucinations and RBD, 16,21,36,37 and in one study RBD was a predictor of future psychosis. 13 Additionally, compared to those without hallucinations, PD subjects with hallucinations are more likely to have daytime somnolence, 7 severe sleep fragmentation, 37,38 and vivid dreams. 37,39 Recognition of sleepwake dysregulation in PD with hallucinations led to the hypothesis that hallucinations were caused by intrusion of dream imagery into wakefulness.…”
Section: Sleep Disorders and Autonomic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation